Geographical variation in egg size dimorphism in rockhopper penguins - Demongin, Laurent; Poisbleau, Maud; Raya Rey, Andrea Nélida; Schiavini, Adrian Carlos Miguel; Quillfeldt, Petra; Eens, Marcel; Strange, Ian J. (Polar Biology)
All crested penguins present a unique reversed hatching asynchrony: the larger second-laid egg (B-egg) hatches before the smaller first-laid egg (A-egg). Although both eggs often hatch, the A-chick generally dies of starvation within days after hatching. However, within rockhopper penguins, the population at the Falkland Islands is unique in that some birds manage to raise both chicks. Although it has been suggested that the egg size dimorphism between A- and B-eggs may explain how long both eggs and chicks survive, this hypothesis has never been explicitly tested. We expect that both eggs are retained longer in the less dimorphic clutches than in the more dimorphic ones. In this paper, we have compiled egg measurements for three rockhopper penguin species (Eudyptes chrysocome, E. filholi and E. moseleyi) in order to compare the intra-clutch egg size dimorphism among these species. Furthermore, we have collected new data to compare egg size dimorphism between two populations of E. chrysocome (Falkland Islands versus Staten Island). A-egg volumes are more variable between species and populations than B-egg volumes. E. chrysocome and especially the population from the Falkland Islands produces the largest A-eggs and the least dimorphic eggs. Nevertheless, as differences in A-egg volumes between species and between the populations of Falkland Islands and Staten Island are stronger and more significant than differences in egg dimorphism, we suggest that A-egg volume, more than egg dimorphism, could be one of the factors influencing the prevalence of twins. A large A-egg and/or reduced egg dimorphism is probably necessary to enable rockhopper penguins to raise two chicks, but other reasons may also be involved which enable them to keep both eggs and chicks. Fil: Demongin, Laurent. Max Planck Institute für Ornithologie; Alemania Fil: Poisbleau, Maud. Max Planck Institute für Ornithologie; Alemania Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de ...